The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1152/ajpregu.00126.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary TNF-α overexpression on mouse isolated skeletal muscle function

Abstract: Zuo L, Nogueira L, Hogan MC. Effect of pulmonary TNF-␣ overexpression on mouse isolated skeletal muscle function. Am J Physiol Regul Integr Comp Physiol 301: R1025-R1031, 2011. First published June 22, 2011 doi:10.1152/ajpregu.00126.2011.-TNF-␣ is a proinflammatory cytokine that is involved in numerous pathological processes including chronic obstructive pulmonary disease (COPD). In the present study, we used a transgenic mouse model that overexpresses TNF-␣ in the lung (Tg ϩ ) to test the hypothesis that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…An interesting hypothesis on molecular level is increased reactive oxygen species formation and oxidative stress (Zuo et al, 2012). This could lead to increased TNF α levels, which reduce skeletal muscle force and resistance to fatigue (Zuo, Nogueira & Hogan, 2011). As a systemic inflammatory disorder, COPD is associated with respiratory muscle dysfunction (Wouters, 2002) which could be further worsened by this mechanism and contribute to the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting hypothesis on molecular level is increased reactive oxygen species formation and oxidative stress (Zuo et al, 2012). This could lead to increased TNF α levels, which reduce skeletal muscle force and resistance to fatigue (Zuo, Nogueira & Hogan, 2011). As a systemic inflammatory disorder, COPD is associated with respiratory muscle dysfunction (Wouters, 2002) which could be further worsened by this mechanism and contribute to the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…So the question is whether circulating or lung-derived TNF-/ would have an impact on muscle function. In a transgenic mouse model overexpressing TNF-/ in the lung, TNF-/ impaired peripheral skeletal muscle function due to excessive formation of superoxide in contracting skeletal muscle [36,37]. However, a study of 426 COPD patients over a 3-year period found that TNF-/ levels were associated with muscle loss only in patients who were cachectic at entry into the study; the authors concluded that inflammation is a consequence rather than a cause of initial loss of fat-free mass [38].…”
Section: Copdmentioning
confidence: 99%
“…It appears that this cytokine may be a key factor in reducing contractile function of the heart, diaphragm, and limb muscles (28,45,59). Specifically, pulmonary TNF-␣ overexpression has been shown to induce peripheral skeletal muscle dysfunction (60) and impair muscle regeneration (27). However, the mechanism by which this occurs has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have investigated the potential link between TNF-␣ and ROS formation in skeletal muscle. We used a pulmonary TNF-␣ overexpression (Tg ϩ ) mouse to model COPD conditions, as previously described (16,60), and to delineate the role of ROS in a contracting peripheral skeletal muscle (soleus) affected by TNF-␣ overexpression in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation